Hyperuricemia and associated factors among adult cardiovascular disease patients at Salale University Comprehensive Specialized Hospital, Fitche, Central Ethiopia - Negesse Bokona Rufe; Tolera Ambisa Lamesa; Aklilu Getachew Mamo; Belay Merkeb Zewude; Bedasa Addisu; Deresa Jamma Nigusie; Sintayehu Asaye Biya (PLoS ONE, 2025)
Background Despite evidence suggesting that hyperuricemia (serum uric acid >7.0 mg/dL in males and >6.0 mg/dL in females) contributes to adverse outcomes like mortality and hospitalization in patients with cardiovascular disease (CVD), a comprehensive understanding of its magnitude is still lacking, underscoring the need for further investigation. There is no previously published study about hyperuricemia in cardiovascular disease in Ethiopia. Therefore, this study aims to investigate the prevalence of hyperuricemia and its associated factors among adult patients with cardiovascular diseases at Salale University Compressive Specialized Hospital Located in Fitche, Ethiopia (115 km north of Addis Ababa),from October 1, 2023, to January 28, 2024. Materials and methods A hospital-based cross-sectional study was conducted on 298 participants with different types of cardiovascular disease. The participants were selected using a consecutive sampling technique. Socio-demographic factors were collected using interviewer-administered questionnaires, while overnight blood samples were collected and biochemical tests were analyzed using the COBAS c 311 automated clinical chemistry analyzer. Descriptive statistics and logistic regression analyses were performed. A variable that had a p-value of ≤ 0.05 with a 95% confidence interval was considered statistically significant. Result The prevalence of hyperuricemia among adult cardiovascular disease patients was 41.3% CI [35.6–47.1]. The highest prevalence of hyperuricemia was found among cardiovascular disease patients with congestive heart failure (48.0%) and hypertensive heart disease (41.2%). Factors such as physical activity (AOR: 4.1; 95% CI: 1.5–10.7, P = 0.004), dyslipidemia (AOR: 2.7; 95% CI: 1.2–6.0, P = 0.01) and chronic kidney disease (AOR: 3.1; 95% CI: 1.5–6.1, P = 0.001) were found to be associated with hyperuricemia among individuals with cardiovascular disease. Conclusion The study indicated a high prevalence of hyperuricemia among participants with cardiovascular disease. Physical activity, dyslipidemia, and chronic kidney disease were recognized as significant associated factors of hyperuricemia among cardiovascular disease. Therefore, early diagnosis of hyperuricemia and its management is essential to control complications and extend the life expectancy of individuals with cardiovascular disease.